The Effects of Forest Types and Canopy Cover on the Thermal Environment of the Large Tree-shrew (Tupaia tana) - Yap, Pui Kwan (Universiti Malaysia Sarawak (UNIMAS), 2015)
Thermal environment affects the physiological responses of animals due to its effects on metabolism. Most of the studies about climate change on thermal environment of mammals took place on Northern hemisphere rather than tropical region. This study will help to fill in gap on our knowledge and using nighttime rest-phase temperature as a proxy for overall costs of living in forests. The study was carried out in Singai forest and UNIMAS forest. The percentage of canopy coverage will be calculated. The Tupaia tana was caught by using cage traps and radio collar was put on their neck to record their habitat usage. The ambient temperature and the nest sites temperature was obtained by placing DS 19922 Thermocron iButtons in various locations such as tree holes and located nest sites in each site to monitor the surrounding temperature. The metabolic costs of Tupaia tana was measured under current ambient as the global temperature is predicted increase by 4 °C on next century. There were no significant in canopy coverage for both forests but there were significant in ambient temperatures.